An analysis of acromioclavicular joint morphology as a factor for shoulder impingement syndrome. Issue 3 (July 2014) - Colegate-Stone, Toby J; Tavakkolizadeh, Adel; Sinha, Joydeep
Background: The present study aimed to determine whether acromioclavicular (AC) joint morphology was a factor in the development of symptomatic impingement necessitating AC joint excision. Methods: We performed a prospective cohort study on all patients undergoing AC joint excision for symptomatic joint pain unresponsive to conservative treatment between 2009 and 2011. This involved 106 consecutive patients (57 women, 49 men, average age 54 years, age range 33 to 76 years). Prior to surgery, radiographic classification of the AC joint was performed producing three main groups: oblique, flat or curved. Pre- and postoperative assessment was performed using the Oxford Shoulder Score and the Disabilities of the Arm, Shoulder and Hand questionnaire. Results: A significantly ( p  < 0.05) higher frequency of oblique AC joint morphology was seen in the AC joint excision study population compared to the normal population. Postoperative outcome demonstrated no significant difference ( P  > 0.05) between any of the three AC joint morphologies. Conclusions: The present study demonstrates a significant association between the oblique AC joint morphology and those patients who develop AC joint pain requiring surgery. Outcomes of surgery were independent of joint morphology, gender or age, with all patient subgroups demonstrating significant improvement by the end of the study.